COMMISIONING AND FAT HVAC FOR OFFSHORE ON THE KLA FLOW STATION - Yusup Firdaus; Engkos Koswara (Jurnal Mekanika dan Manufaktur, 2022)
HVAC stands for Heating Ventilation Air Conditioning, in the industrial world it is very necessary to condition a room according to its needs, it can be used to regulate a room or freeze a product, the selection of HVAC materials for Offshore is very important so that the unit lasts a long time and does not rust easily. The importance of selecting materials that are in accordance with the provisions in terms of safety, function and quality, materials that are easy to obtain, sizes according to calculations, aesthetics, and materials that are not easy to rust. commissioning is done because to determine the quality and function of the HVAC unit whether it is in accordance with the design, function or calculation